Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1994)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1990)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1984)

Report of Sex Education Committee - Quebec Federation of Protestant Home & School Associations (1967)
The term "sex education" as used in the terms of reference has been interpreted by the committee to mean education in which sexual, biological and physiological facts are only disclosed in the full context of human relations. It must be made clear at the outset therefore, that sex education, in our opinion, cannot consist of less than education in Human Relations in which sexual growth is seen as part of the whole growth of the individual and in which basic sexual facts are discussed in the context of the growing boy and girl in their development into manhood and womanhood.

Sexual Assault - Black Community Resource Centre (BCRC)